An applied dynamic structural macro-econometric model for Rwanda. Issue 4 (2nd October 2022) - Geda, Alemayehu; Yimer, Addis
Abstract: This study develops a macro-econometric model for a typical supply constrained African economy aimed at developing a theoretical and empirical template for such policy tools that are increasingly being demanded by African ministries of finance and central banks. We concretised it by building a macro-econometric model for Rwanda. The model is designed to capture the structural characteristics of such an African economy. The Rwanda macro-econometric model has 107 equations of which 72 are endogenous. In addition, we also build a supplementary ARIMA based model with 33 equations for the exogenous variables to make the model useful for forecasting. We disaggregate the fiscal, balance of payments and money supply blocks of the model to offer an adequate picture of the macro-economy. We also do an econometric estimation of the core behavioural equations of the model using the error correction modelling approach for the period 1960–2009. The model can be easily extended further to support the budgeting, forecasting and macroeconomic policy analyses in the relevant ministries and central banks in Africa. We successfully solve the model and reproduce historical values from 1999 to 2009 and forecast major macro-variables for 2010 to 2015. We also use the model to conduct policy and external shock simulation exercise that are important for policymakers.